Unmet Health Services Needs Among US Children with Developmental Disabilities: Associations with Family Impact and Child Functioning. Issue 9 (November 2016) - Lindly, Olivia J.; Chavez, Alison E.; Zuckerman, Katharine E.
ABSTRACT: Objective: To determine associations of unmet needs for child or family health services with (1) adverse family financial and employment impacts and (2) child behavioral functioning problems among US children with autism spectrum disorder (ASD), developmental delay (DD), and/or intellectual disability (ID). Method: This was a secondary analysis of parent-reported data from the 2009 to 2010 National Survey of Children with Special Health Care Needs linked to the 2011 Survey of Pathways to Diagnosis and Services. The study sample (n = 3, 518) represented an estimated 1, 803, 112 US children aged 6 to 17 years with current ASD, DD, and/or ID (developmental disabilities). Dependent variables included adverse family financial and employment impacts, as well as child behavioral functioning problems. The independent variables of interest were unmet need for (1) child health services and (2) family health services. Multivariable logistic regression models were fit to examine associations. Results: Unmet need for child and family health services, adverse family financial and employment impacts, and child behavioral functioning problems were prevalent among US children with developmental disabilities. Unmet needs were associated with an increased likelihood of adverse family employment and financial impacts. Unmet needs were associated with an increased likelihood of child behavioral functioning problems the following year; however, this association was not statistically significant. Conclusion: Unmet needs are associated with adverse impacts for children with developmental disabilities and their families. Increased access to and coordination of needed health services following ASD, DD, and/or ID diagnosis may improve outcomes for children with developmental disabilities and their families.